Health education in Diabetes mellitus control: The role of nurses in Primary Care (Research, Society and Development, 2025)
The present study focuses on health education in diabetes control, emphasizing the role of nurses in Primary Health Care. The general objective was to analyze how nurses contribute to the control and prevention of diabetes through educational actions aimed at self-care and patients’ therapeutic adherence. The research was characterized as an integrative literature review, carried out through a search of studies in the SciELO, LILACS, and MEDLINE/PubMed databases between 2019 and 2025, resulting in the selection of 16 articles. The results and discussion showed that nurses play an essential role in health education by using pedagogical and communicative strategies that strengthen self-care, treatment adherence, and the prevention of diabetes-related complications. Individual and group educational actions proved effective in improving patients’ quality of life, reducing cases of decompensation and hospitalizations. However, the studies also pointed out challenges such as work overload, lack of resources, and the need for greater pedagogical training of nurses to act as health educators. It is concluded that the educational role of nurses is indispensable in Primary Care, making it necessary to strengthen public policies for continuing education, expand the structure of Basic Health Units, and encourage the use of digital technologies in monitoring diabetic patients. Thus, health education is configured as an effective tool to improve care, promote patient autonomy, and contribute to strengthening the public health system.